Dental and Oral Care Treatment Needs in Children with Down Syndrome in Surabaya - Ardianti Maartrina Dewi; Tania Saskianti; Mega Moeharyono Puteri (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Aims of this study was to observe dental and oral care treatment needs of Down Syndromechildren who are members of the Parents’ Association of Children with Down Syndrome (POTADS) inSurabaya. Material and Methods: This study used secondary data from dental and oral examinationrecords of total sample 34 Down Syndrome children aged 5-17 years who attended community serviceprogram “SPECIAL CHILDREN DENTAL VISIT -1” from August to October 2017. Results: Only fewsamples showed good oral hygiene though most of them brushed their teeth twice a day which likely relatedto physical and mental limitations. Most samples had cariogenic dietary habits with def-t/DMF-T scorewere below 10. Malocclusion founded can be worsen by oral bad habits which has existed in most samples.Conclusion: From this study it can be concluded that the most indicative treatment for Down Syndromechildren are restorations and extractions.Good collaboration between parents and caregivers is needed toprevent more severe oral health problems which need more complex dental treatment. Children with DownSyndrome are entitled to the opportunity to develop and get special services, including in terms of oralhealth. With good oral health, the quality of life of Down Syndrome children can improve.